An analysis on the behavioural traits of salaried class investors in Tamil Nadu. (13th January 2010) - Kasilingam, R.; Jayabal, G.
Investors exhibit different types of behavioural traits when they are involved in the investment activities like information search, evaluating investment avenues and reviewing the investment made. These behavioural traits might vary from individual to individual. To identify these behavioural traits 37 statements were used with five point Likert scale to collect opinion from investors. Some of the behavioural traits identified from this research are commitment, rationale, variety seeking, dissonance reducing and external locus control. These behavioural traits have impact on investor's decision. Therefore, studying behavioural traits is important for the investment intermediaries who offer investment instruments.